2020
DOI: 10.1016/j.buildenv.2020.107323
|View full text |Cite
|
Sign up to set email alerts
|

Modeling transient particle transport in transient indoor airflow by fast fluid dynamics with the Markov chain method

Abstract: It is crucial to accurately and efficiently predict transient particle transport in indoor environments to improve air distribution design and reduce health risks. For steady-state indoor airflow, fast fluid dynamics (FFD) + Markov chain model increased the calculation speed by around seven times compared to computational fluid dynamics (CFD) + Eulerian model and CFD + Lagrangian model, while achieving the same level of accuracy. However, the indoor airflow could be transient, if there were human behaviors inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Due to the lack of experimental data on the fluid dynamics of COVID-19 infected droplets, reviewing the available simulations on spreading the droplet through sneezing/coughing are helpful for a better understanding of modeling the COVID-19 transmission. Laminar, transient, and turbulent indoor airflow significantly affect the dispersion and transport of suspended droplets ( Liu et al, 2020 , Liu et al, 2020 , Liu and Chen, 2018 ). Furthermore, the indoor airflow becomes transient due to human behaviors involving walking, coughing, or sneezing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of experimental data on the fluid dynamics of COVID-19 infected droplets, reviewing the available simulations on spreading the droplet through sneezing/coughing are helpful for a better understanding of modeling the COVID-19 transmission. Laminar, transient, and turbulent indoor airflow significantly affect the dispersion and transport of suspended droplets ( Liu et al, 2020 , Liu et al, 2020 , Liu and Chen, 2018 ). Furthermore, the indoor airflow becomes transient due to human behaviors involving walking, coughing, or sneezing.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the direction of the cough and the area of mouth opening during coughing was not related to physiological parameters such as height, weight, and gender. The effects of human expiratory flows on respiratory infection in ventilated environments are investigated by Liu et al, 2020 , Liu et al, 2020 to minimize the infection risk of breathing. Their results indicated the large droplets deposit within a short distance and are hardly affected by the thermal stratification; however, droplet infection to the susceptible people could happen at close contact with the infector.…”
Section: Introductionmentioning
confidence: 99%
“…Their results can provide high quality data for validating CFD models. In recent study, Liu et al [ 26 ]developed fast fluid dynamics with the Markov chain method to model the transient particle transport in transient indoor airflow. With this new method, the computational time was 7.8 times less than that of the CFD + Eulerian method.…”
Section: Introductionmentioning
confidence: 99%
“…Abuhegazy et al provided a CFD simulation of a classroom in FLUENT and a detailed discussion on how windows, glass barriers as well as aerosol size and source might effect the particle trajectories [18]. Other CFD studies have considered the impact of ventilation on the distribution of aerosols from coughing using a commercial software [19] and particle trajectories in OpenFOAM [20] as well as utilizing far-UVC lightning as a virus inactivator [21]. Furthermore, various elements impacting the spread of airborne particles, such as ventilation, air filters and masks, have been considered in assorted CFD publications [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%